Gender-sensitive value chain intervention improved profit efficiency among orange-fleshed sweetpotato producers in Rwanda - Bocher, T.; Low, Jan W.; Sindi, K.; Rajendran, S. (Walter de Gruyter GmbH, 2017)
The Rwanda Super Foods project sought to develop a value chain for processed orange-fleshed sweetpotato products to respond to farmer concerns over lack of markets. This study used data collected from five districts in rural Rwanda under supper food project between August and September 2014. The study applied a stochastic profit frontier model to data collected from 846 households growing sweetpotato, among which 327 were value chain participants; 312 were “spillover” households that received planting material from participant households, and the remainder control households with no project links. Results showed that average level of profit efficiency in sweetpotato production systems is 55%; suggesting that an estimated 45% of profit is lost due to the combined effect of technical, allocative and scale inefficiency. The profit efficiency of participant households was 64% compared to 20% of the control households. Moreover, the profit efficiency of the female beneficiary, female spillover, and male beneficiary households was found to be 55%, 70%, and 90% against 17% for male control households, respectively. Findings suggest that an orange-fleshed sweetpotato based value chain intervention can enhance the profit efficiency of the poor and disadvantageous households, if designed with special attention to women’s needs. Thus, polices and programs aiming at improving the livelihood of smallholder should be designed targeting women and resource poor.